Bela as the Cultural Sacrification of the Implementation of Aqiqah and Tasyakuran in Gowok Kepuh Village, Serang City (Studi Living Qur’an) - Tamimi Setia Alam; Sholahuddin Al Ayubi; Ade Fakih Kurniawan (Program Magister Ilmu Al-Qur'an dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2024)
This study examines the phenomenon of cultural sacralization in the implemen-tation of aqiqah and tasyakuran in Gowok Kepuh Village, Sukajaya Village Curug District, Serang City, with the Living Qur'an Study approach. Aqiqah and Tasyakuran are religious practices in Islam that involve giving qurbani as an expression of gratitude to Allah for the birth of a child. The main objective of this study is to understand how the culture of aqiqah and tasyakuran is an integral part of the life of the local community and the extent to which the influence of religion and local wisdom interact in the implementation of this ritual. This study adopts a qualitative descriptive method with the Living Qur'an Study approach that emphasizes the understanding of religion in the context of daily life. Data were obtained through participatory observation, interviews, and analysis related to aqiqah and tasyakuran rituals. The findings of the study indicate that the implementation of aqiqah and tasyakuran in Gowok Kepuh Village has experienced a strong cultural sacralization, where local practices and religious values blend with each other such as the sacrifice of goats and chickens at the same time, the presence of candles, scissors, fragrances, water, and young coconuts The findings of this study can provide deeper insights into how local culture and religion can influence each other in the context of the implementation of religious rituals, as well as the relevance of the Living Qur'an Study in understanding and explaining this phenomenon. This research can also provide a more comprehensive view of social and religious dynamics in the community of Gowok Kepuh Village, Sukajaya Village, Curug District, Serang City.